Method for ultrasonically optimizing structure and performance of Ni-Co-based high-temperature alloy

Through wall vibration ultrasonic treatment and heat treatment processes, the solidification structure of Ni-Co-based high-temperature alloy is regulated, and the problems of alloy structure defects and weakened mechanical properties in the prior art are solved, thereby achieving efficient tissue optimization and performance improvement of the alloy.

CN119410959APending Publication Date: 2025-02-11NORTHWESTERN POLYTECHNICAL UNIV

Patent Information

Application Number
CN202411545372.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The prior art is difficult to regulate the distribution of primary γ phase and Al elements by power ultrasonication, resulting in alloy structure defects and weakening its mechanical properties.

Method used

The high-temperature melt of Ni-Co-based high-temperature alloy is treated with wall vibration ultrasonic treatment, and the ultrasonic application stage, vibration mode and cooling rate are regulated during the solidification process, and combined with the heat treatment process, the cast structure and mechanical properties of the alloy are optimized.

Benefits of technology

Through ultrasonic optimization, the γ-phase grains are significantly refined, the (γ+α) eutectic structure is formed, the volume fraction and size of the γ-phase are improved, the grain boundary strengthening effect is enhanced, and the tensile strength and high-temperature performance of the alloy are significantly improved. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410959A_ABST
    Figure CN119410959A_ABST
Patent Text Reader

Abstract

The invention provides a method for ultrasonically optimizing the structure and performance of a Ni-Co-based high-temperature alloy. The method comprises the following steps: 1, smelting a Co block, a Ni block, a Cr block and an Al block twice and preserving heat to obtain an alloy melt; secondly, the temperature of a preheating casting mold reaches 900 DEG C or above; thirdly, the alloy melt is poured into a preheated casting mold, then ultrasonic vibration treatment with the frequency of 17-25 kHz is conducted on the alloy melt contained in the casting mold, the cooling speed is controlled, and an alloy ingot is obtained; and fourthly, the alloy ingot is subjected to heat treatment, and the structure and performance of the Ni-Co-based high-temperature alloy are further improved. According to the method, the Ni-Co-based alloy melt is subjected to wall vibration type treatment by adopting ultrasonic waves, a proper smelting-pouring system is formulated according to the thermophysical property of the alloy, and an experimental scheme of effectively applying ultrasonic waves in a segmented manner and controlling cooling is implemented for different phase change stages and solidification structures, so that the as-cast solidification structure and the mechanical property of the Ni-Co-based alloy are regulated and controlled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of high-temperature alloys, and in particular relates to a method for ultrasonically optimizing the structure and performance of a Ni-Co based high-temperature alloy. Background Art

[0002] Nickel-based high-temperature structural materials are widely used in the manufacture of important parts such as advanced aero engines and gas turbines due to their high temperature bearing capacity, excellent high-temperature oxidation resistance, corrosion resistance and excellent application reliability. This is mainly attributed to the typical microstructure of refined Ni (face-centered cubic γ) matrix phase and Ni3Al (L12 precipitation phase γ′ phase) embedded in the γ phase. The new Ni-Co-based high-temperature alloy has good stability due to the addition of high-melting point Co, making it the preferred material for the new generation of aero engines. The microstructure of the cast Ni-Co-based alloy is a Ni-rich solid solution γ (Ni) phase, with a small amount of nano-scale γ′ particle phase precipitated on the γ phase. The main problems of the current cast Ni-Co-based alloy are: 1. The primary γ phase dendrites are coarse; 2. The precipitated γ′ phase is too little; 3. The positive segregation of Al elements between dendrites weakens the grain boundaries. These three aspects of structural defects weaken the mechanical properties of the alloy, such as strength, plasticity, creep resistance and impact resistance. Commonly used methods to improve the structure and properties of nickel alloys include adding refiners, optimizing alloy smelting and solidification processes, and improving heat treatment systems. However, adding refiners and adjusting the melting-solidification process cannot simultaneously control the size of the γ phase, the segregation of Al elements at the grain boundary, and the volume fraction of the γ′ phase, and there are disadvantages such as impure alloy composition and complex operation process. On the other hand, rolling deformation after heat treatment is currently a necessary means of strengthening nickel-based alloys, but many precision casting parts have high requirements on shape and size, so deformation treatment cannot be used, which makes improving the performance of cast Ni-Co-based alloys an urgent problem to be solved.

[0003] Applying vibration during the solidification process of metals or alloys is one of the most effective ways to improve their structure and performance. Power ultrasound is a form of transmission of ultra-high mechanical vibration energy of objects. It has significant physical properties such as high frequency, high power density, good beam and directionality. When interacting with liquid, semi-solid metals or alloys, there are a series of nonlinear ultrasonic effects such as pressure field, thermal effect, acoustic cavitation and acoustic streaming, thereby achieving the effects of purifying the melt, refining grains and homogenizing the structure.

[0004] The current limitations of the application of power ultrasound in the solidification process of nickel-based alloys are: 1. Due to the temperature limit of the amplitude transformer in contact with the melt, it is still impossible to use power ultrasound to treat Ni-Co-based high-temperature alloys with a melting temperature of 1400-1600℃, making it difficult to effectively control the primary γ phase and Al element distribution by affecting the liquid-solid phase transition. 2. Ultrasound is difficult to affect the solid-state phase transition of the alloy and cannot effectively control the precipitation process of the γ′ phase. In fact, it is not as simple as you think that the larger the ultrasonic amplitude, the better the effect of ultrasonic treatment of alloy solidification structure and performance. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for ultrasonically optimizing the microstructure and properties of Ni-Co based high temperature alloys in view of the above-mentioned deficiencies in the prior art. The method uses wall-vibration ultrasonic treatment of the Ni-Co alloy high temperature melt, in-situ controls the ultrasonic application stage, vibration mode and cooling rate during the solidification process, and finally controls the heat treatment process of the cast alloy under different ultrasonic conditions, so as to achieve the purpose of effectively improving the solidification microstructure and mechanical properties.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for ultrasonically optimizing the structure and performance of a Ni-Co-based high-temperature alloy, characterized in that the Ni-Co-based high-temperature alloy is composed of the following components in atomic percentage: Co: 20-25%, Cr: 13-15%, Al: 11-13%, and the balance is Ni and unavoidable impurities; the method comprises:

[0007] S1, Ni-Co based high temperature alloy smelting: Co block, Ni block and Cr block are taken in proportion and placed in crucible 1 for the first smelting and heat preservation, and a solidified Ni-Co-Cr master alloy is obtained after the first smelting and heat preservation, and then the Ni-Co-Cr master alloy and Al block are placed in crucible 2 for the second smelting and heat preservation to obtain an alloy melt;

[0008] S2. Preheating the mold: first evenly apply boron nitride or zinc oxide release agent on the inner wall of the mold and dry it, then preheat the mold, the preheating temperature is higher than 900°C;

[0009] S3. Ultrasonic optimization to prepare alloy ingots: The alloy melt obtained in S1 is poured from the crucible 2 into a preheated casting mold, and then the alloy melt in the casting mold is subjected to ultrasonic vibration treatment at a frequency of 17-25 kHz, and the cooling rate is controlled to finally obtain an alloy ingot.

[0010] Preferably, the alloy ingot obtained in S3 is heat treated to further optimize the structure and properties of the Ni-Co based high temperature alloy.

[0011] Preferably, the specific process of the first smelting and heat preservation is: first, Co block, Ni block, and Cr block are placed in order into the crucible 1, wherein the Cr block is not in direct contact with the inner wall of the crucible 1, the material of the crucible 1 is graphite or ceramic with a temperature resistance of more than 2000°C, and the crucible 1 needs to be sprayed with a boron nitride coating before use, and the raw materials are melted under vacuum conditions, and the high-frequency power supply is turned off after the raw materials are completely melted and kept at 1600-1550°C for 3 minutes, and the alloy is cooled with the furnace to obtain a Ni-Co-Cr master alloy;

[0012] The specific process of the second smelting and heat preservation is: first wrap the Ni-Co-Cr master alloy with aluminum foil, then put it into the crucible 2 sprayed with a high-temperature resistant coating, the material of the crucible 2 is graphite or corundum, and smelt it in the air. After the master alloy is completely melted, put the Al block into the melt, and keep it at 1530-1570°C for 1-2 minutes to obtain an alloy melt.

[0013] Preferably, in S3, according to the requirements of the metallographic structure in the alloy, there are four ways to treat the alloy melt by ultrasonic vibration, and different cooling control methods are used, specifically:

[0014] First, when ultrasonic vibration acts only on the refinement of the primary γ phase, ultrasonic vibration is started before the alloy melt is poured into the casting mold, and one-dimensional ultrasound with an amplitude of less than 14 μm is applied. When the temperature of the alloy melt drops to the end temperature of the L→γ liquid-solid phase transition of 1377-1367°C, the ultrasonic vibration is stopped, and then the alloy melt is controlled to cool to 600°C at a cooling rate of not less than 30°C / s, and then naturally cooled to obtain an alloy ingot;

[0015] Second, when ultrasonic vibration acts on the refinement of the primary γ phase and the formation of the eutectic (γ+α) structure at the same time, the ultrasonic vibration is started before the alloy melt is poured into the casting mold, and ultrasound with an amplitude of not less than 14 μm is applied. When the temperature of the alloy melt drops to the eutectic reaction L→γ+α end temperature of 1321-1311°C, the ultrasonic vibration is stopped, and then the alloy melt is controlled to cool to 600°C at a cooling rate of not less than 30°C / s, and then naturally cooled to obtain an alloy ingot;

[0016] Third, when ultrasonic vibration only acts on the precipitation and growth of the γ′ phase, after the alloy melt is poured into the casting mold, when the temperature naturally drops to the precipitation temperature of the γ′ phase at 1050-1035°C, ultrasonic vibration is started, and ultrasonic vibration with an amplitude of not less than 14μm is applied until the alloy melt temperature drops to the γ′ phase complete precipitation temperature of 890-840°C, and then the ultrasonic vibration is immediately turned off. At this time, the alloy melt is controlled to cool to 600°C at a cooling rate of 10-20°C / s, and then naturally cooled to obtain an alloy ingot;

[0017] Fourthly, when ultrasonic vibration acts on the whole process of primary γ phase, eutectic (γ+α) solidification and precipitation and growth of γ′ phase, ultrasonic vibration is turned on before the alloy melt is poured into the casting mold, and intermittent ultrasound with an amplitude of not less than 14 μm is applied. When the temperature of the alloy melt drops to the alloy solidification temperature of 1321-1311°C, the ultrasonic vibration is stopped, and then the alloy melt is controlled to be cooled to the γ′ phase precipitation start temperature of 1050-1035°C at a cooling rate of not less than 30°C / s, and then ultrasonic vibration is turned on again, and intermittent ultrasound with an amplitude of not less than 14 μm is applied. When the temperature of the alloy melt drops to the γ′ phase complete precipitation temperature of 890-840°C, the ultrasonic vibration is immediately turned off, and finally the alloy melt is controlled to be cooled to 600°C at a cooling rate of 10-20°C / s, and then naturally cooled to obtain an alloy ingot.

[0018] The present invention uses ultrasonic waves to perform wall vibration treatment on Ni-Co-based alloy melt, and formulates a suitable melting-pouring system according to the thermophysical properties of the alloy, and implements an effective experimental scheme of segmented ultrasonic-controlled cooling for different phase change stages and solidification structures, thereby regulating the cast solidification structure and mechanical properties of the Ni-Co-based alloy. In order to further improve the performance of the alloy, different heat treatments are performed on the cast alloy structure under ultrasonic conditions.

[0019] Preferably, the intermittent ultrasound is a plurality of ultrasound treatments with intervals in which ultrasonic vibration is not applied, a single ultrasound treatment lasts for 1-5 seconds, and the interval in which ultrasonic vibration is not applied does not exceed 1 / 2 of the single ultrasound treatment time.

[0020] Preferably, if the heat treatment is to uniformly distribute the eutectic (γ+α) structure, the heat treatment temperature is 1050-1200° C., the holding time is 3.5-4.5 h, and the alloy is cooled in the furnace or naturally cooled in the air;

[0021] If the heat treatment is to promote the full precipitation of the nano-scale γ′ phase, the heat treatment temperature is 650-800° C., the insulation time is 16-32 hours, and after the insulation is completed, the alloy is quickly taken out and placed in quenching oil to cool to room temperature.

[0022] Preferably, the outer mold sleeve of the casting mold is provided with a cooling jacket through which cooling gas passes.

[0023] Preferably, the mold in S2 is preheated by a high-frequency induction heating coil, the maximum diameter of the high-frequency induction heating coil is 5-10 mm smaller than the side length of the inner cavity of the mold, and the height of the high-frequency induction heating coil is 60-75% of the inner height of the mold; during preheating, the high-frequency induction heating coil is placed in the center of the inner cavity of the mold in the horizontal direction and 3-5 mm away from the bottom of the mold in the vertical direction.

[0024] Preferably, S1 and S2 use infrared thermometers, and S3 uses thermocouples to monitor temperature changes.

[0025] Preferably, the mass purity of the Co block, Ni block, Cr block and Al block in S1 is not less than 99.99%.

[0026] Compared with the prior art, the present invention has the following advantages:

[0027] 1. The two-step smelting method of Ni-Co based alloy provided by the present invention firstly melts the refractory alloy separately in a vacuum protection atmosphere, thereby solving the problem of uneven smelting of high melting point components; secondly, the Ni-Co-Cr master alloy and Al raw material are smelted in air, thereby reducing the chemical combination temperature of the alloy to avoid high temperature loss of Al and improving the smelting efficiency.

[0028] 2. The ultrasonic optimization method for the microstructure and performance of Ni-Co-based high-temperature alloy provided by the present invention applies an ultrasonic field during the liquid-solid phase transition to change the solidification path and microstructure of the alloy. Under static conditions, the alloy undergoes liquid-solid phase transition to generate a primary γ phase with a dendrite size of about 1690 μm; after applying ultrasound, the γ phase grain size is refined to less than 20% of that before treatment, and at the same time, an L→α+γ eutectic reaction occurs between dendrites to form a (γ+α) eutectic structure with a volume fraction of up to 10%, thereby improving the grain boundary strengthening effect.

[0029] 3. The method for ultrasonic optimization of Ni-Co-based high-temperature alloy structure provided by the present invention applies ultrasound during the solid-state phase transformation from γ to γ′, and combines it with corresponding cooling control to achieve the regulation of the volume fraction and size of the γ′ precipitated phase. Under static conditions, the volume fraction of the γ′ particle phase is less than 10%, and the diameter is about 40 to 60 nm. Ultrasound promotes the precipitation and growth of a large number of nano-scale γ′ phases, and the volume fraction and size reach 35 to 55% and 50 to 80 nm, respectively. The substantial increase in the volume fraction of the γ′ phase improves the precipitation strengthening effect.

[0030] 4. The method for ultrasonic optimization of Ni-Co-based high-temperature alloy structure provided by the present invention changes the segregation degree of Al in dendrites and between dendrites after applying ultrasonic field in liquid alloy. Under static solidification, a large amount of Al element segregates between dendrites of γ phase. After applying ultrasound, Al tends to be enriched in dendrites, strengthening the γ phase grain boundary.

[0031] 5. The tensile strength of the alloys prepared by the method of the invention, both unheat-treated and heat-treated, is improved at room temperature and high temperature (650°C), and is superior to that of commonly used cast nickel-based alloys such as IN718 and IN625.

[0032] In summary, the present invention uses ultrasonic waves to perform wall vibration treatment on Ni-Co-based alloy melt, and formulates a suitable melting-pouring system according to the thermophysical properties of the alloy, and implements an effective experimental scheme of segmented ultrasonic-controlled cooling for different phase change stages and solidification structures, thereby regulating the cast solidification structure and mechanical properties of the Ni-Co-based alloy. In order to further improve the performance of the alloy, different heat treatments are performed on the cast alloy structure under ultrasonic conditions.

[0033] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The unheat-treated Ni prepared in Example 1 and Comparative Example 1 of the present invention is 50 Co 23 Cr 14 Al 13 Alloy structure morphology pictures: (a) Comparative Example 1; (b) Example 1; (c) Ni prepared in Comparative Example 1 50 Co 23 Cr 14 Al 13 (d) Ni prepared in Example 1 50 Co 23 Cr 14 Al 13 Magnified image of the γ′ precipitation phase in the alloy.

[0035] Figure 2 Ni prepared in Example 1 and Comparative Example 1 of the present invention 50 Co 23 Cr 14 Al 13 DSC spectrum of the alloy.

[0036] Figure 3 The Ni prepared in Example 1 and Comparative Example 1 50 Co 23 Cr 14 Al 13 Surface distribution of Al element in alloy: (a) Comparative Example 1; (b) Example 1.

[0037] Figure 4 Ni after solidification and heat treatment in Example 1 of the present invention 50 Co 23 Cr 14 Al 13 Alloy microstructure images: (a) solidified state; (b) heat treated state.

[0038] Figure 5 Ni prepared in Example 1 and Comparative Example 1 of the present invention50 Co 23 Cr 14 Al 13 Tensile stress-strain curves of the alloy at room temperature (25°C) and high temperature (650°C): (a) Unheat-treated Ni prepared in Example 1 and Comparative Example 1 at room temperature 50 Co 23 Cr 14 Al 13 Alloy, (b) Ni alloy prepared in Comparative Example 1 and Example 1 without heat treatment at 650°C 50 Co 23 Cr 14 Al 13 Alloy, and the heat-treated Ni prepared in Example 1 50 Co 23 Cr 14 Al 13 alloy. DETAILED DESCRIPTION

[0039] Example 1

[0040] This embodiment discloses an ultrasonic optimized Ni 50 Co 23 Cr 14 Al 13 A method for determining the microstructure and properties of a high temperature alloy, the method comprising:

[0041] S1. Alloy smelting: Ni 50 Co 23 Cr 14 Al 13 The atomic ratio of the elements in the alloy is Co: 23%, Cr: 14%, Al: 13%, Ni: 50%, which are converted into the mass percentage of the elements. The surfaces of the raw material blocks are polished to be smooth, and the surface impurities are removed. 89.3g of Ni block with a purity of 99.99%, 41.3g of Co block, 22.2g of Cr block, and 10.7g of Al block are weighed respectively, and smelting and heat preservation are performed twice according to the mass percentage of each element;

[0042] The specific process of two smelting and heat preservation is as follows:

[0043] S101, first put Co block, Ni block and Cr block into crucible 1 in order, wherein the Cr block does not directly contact the inner wall of crucible 1, the material of crucible 1 is ceramic, and crucible 1 needs to be sprayed with boron nitride coating before use, and put into vacuum high frequency furnace after loading, and embed two layers of graphite and mullite insulation sleeves outside crucible 1 respectively, adjust the position of infrared thermometer and close the hatch;

[0044] Then turn on the vacuum pump to evacuate to 10Pa, turn off the vacuum pump and fill the furnace with argon to 360Pa. After repeated vacuuming and filling 3 times, start the first smelting. The current of the high-frequency furnace is 18.4A. After heating for 8 minutes, the temperature reaches 1400℃. Thereafter, the temperature is observed every 0.5min. When the temperature reaches 1600℃, insulation is started. Heating is stopped after 3min. The alloy is cooled in the furnace for half an hour and then the raw materials are taken out to obtain Ni-Co-Cr intermediate alloy.

[0045] S102, first wrap the Ni-Co-Cr master alloy with aluminum foil, then put it into the crucible 2 sprayed with a high-temperature resistant coating, the material of the crucible 2 is graphite or corundum, and a layer of mullite insulation cover is nested outside the crucible 2, and the crucible 2 and the insulation cover are placed in a high-frequency coil and heated with a current of 35A; after the alloy is completely melted, use a long-handled spoon to add Al blocks to the melt and continue smelting. When the temperature of the melt in the crucible 2 reaches 1550°C, the high-frequency current is adjusted to 18A for insulation for 1.5 minutes to obtain an alloy melt, ready for pouring;

[0046] During smelting in S101 and S102, the temperature is detected by an infrared thermometer.

[0047] S2. Preheating the mold: first evenly apply boron nitride or zinc oxide mold release agent on the inner wall of the mold, heat it to 150°C with a hot air gun and dry it, then preheat the mold through the high-frequency induction heating coil with air atmosphere, and remove the high-frequency induction heating coil when the preheating temperature reaches 1000°C;

[0048] The inner dimensions of the casting mold used are 20×20×50 mm, the wall thickness is 6 mm, and the material is TZM alloy.

[0049] During preheating, the high-frequency induction heating coil is placed horizontally at the center of the inner cavity of the mold. The outer diameter of the high-frequency induction heating coil is 12 mm, the height is 35 mm, the bottom of the coil is 3 mm away from the bottom of the mold, the high-frequency induction heating coil is coaxially arranged with the mold, and the infrared thermometer is aligned with the center of the mold.

[0050] S3. Preparation of Ni 50 Co 23 Cr 14 Al 13 Alloy ingot: Before pouring the melt, quickly remove the preheating high-frequency coil in the mold. Use crucible tongs to manually pour the alloy melt obtained in S1 from crucible 2 into the preheated mold, then perform ultrasonic vibration treatment with a frequency of 20kHz on the alloy melt in the mold, and control the cooling rate to finally obtain Ni 50 Co 23 Cr 14 Al 13 Alloy ingots;

[0051] There are four ways to treat the alloy melt with ultrasonic vibration, and they are combined with different cooling control methods, specifically:

[0052] First, when ultrasonic vibration only acts on the refinement of the primary γ phase, ultrasound is started before the alloy melt is poured into the mold, and one-dimensional ultrasound with an amplitude of less than 14 μm is applied. When the temperature of the alloy melt drops to the end temperature of the liquid-solid phase transition of 1377-1367°C, the ultrasonic vibration is stopped, and then the alloy melt is controlled to cool to 600°C at a cooling rate of not less than 30°C / s, and then naturally cooled to obtain Ni 50 Co 23 Cr 14 Al 13 Alloy alloy ingot;

[0053] Secondly, when ultrasonic vibration acts on the refinement of the primary γ phase and the formation of the eutectic (γ+α) structure at the same time, the ultrasound is started before the alloy melt is poured into the casting mold, and one-dimensional or multi-dimensional ultrasound with an amplitude of not less than 14μm is applied. When the temperature of the alloy melt drops to the end temperature of the eutectic reaction L→γ+α of 1321-1311℃, the ultrasonic vibration is stopped, and then the alloy melt is controlled to cool to 600℃ at a cooling rate of not less than 30℃ / s, and then naturally cooled to obtain Ni 50 Co 23 Cr 14 Al 13 Alloy ingots;

[0054] Third, when ultrasound only acts on the precipitation and growth of the γ′ phase, after the alloy melt is poured into the mold, when the temperature naturally drops to the γ′ phase precipitation temperature of 1050-1035°C, ultrasonic vibration is started, and one-dimensional or multi-dimensional ultrasound with an amplitude of not less than 14μm is applied until the alloy melt temperature drops to the γ′ phase complete precipitation temperature of 890-840°C, and the ultrasonic vibration is immediately turned off. At this time, the alloy melt is controlled to cool to 600°C at a cooling rate of 10-20°C / s, and then naturally cooled to obtain Ni 50 Co 23 Cr 14 Al 13 Alloy ingots;

[0055] Fourthly, when ultrasound acts on the whole process of primary γ phase, eutectic (γ+α) solidification and γ′ phase precipitation and growth, ultrasound is turned on before the alloy melt is poured into the mold, and one-dimensional or multi-dimensional intermittent ultrasound with an amplitude of not less than 14 μm is applied. When the alloy melt temperature drops to the alloy solidification temperature of 1321-1311°C, the ultrasonic vibration is stopped, and then the alloy melt is controlled to cool down to the γ′ phase precipitation temperature of 1050-1035°C at a cooling rate of not less than 30°C / s, and then ultrasound is turned on again, and one-dimensional or multi-dimensional intermittent ultrasound with an amplitude of not less than 14 μm is applied. When the alloy melt temperature drops to the γ′ phase complete precipitation temperature of 890-840°C, the ultrasonic power supply is immediately turned off, and finally the alloy melt is controlled to cool down to 600°C at a cooling rate of 10-20°C / s, and then naturally cooled to obtain Ni 50 Co 23 Cr 14 Al 13 Alloy ingot. The intermittent ultrasound is that there is an interval without applying ultrasonic vibration between multiple ultrasonic treatments, the time of a single ultrasonic treatment lasts for 1-5s, and the interval time without applying ultrasonic vibration does not exceed 1 / 2 of the time of a single ultrasonic treatment.

[0056] S4, the Ni obtained in S3 50 Co 23 Cr 14 Al 13 The alloy ingot is heat treated to further improve the Ni 50 Co 23 Cr 14 Al 13 The structure and properties of the alloy; if the heat treatment is to uniformly distribute the eutectic (γ+α) structure of the alloy, the heat treatment temperature is 1050-1200°C, the holding time is 3.5-4.5h, and the alloy is cooled with the furnace or naturally cooled in the air; if the heat treatment is to fully precipitate the nano-scale γ′ phase of the alloy, the heat treatment temperature is 650-800°C, the holding time is 16-32h, and after the holding is completed, the alloy is quickly taken out and placed in quenching oil to cool to room temperature.

[0057] In this embodiment, step S2 performs temperature monitoring by an infrared thermometer, and step S3 uses a thermocouple to measure temperature.

[0058] In this embodiment, the preheated casting mold needs to be connected to a device that can implement ultrasonic vibration in three directions of X, Y, and Z axes. Specifically, the three-dimensional wall-vibration controllable ultrasonic field device disclosed in the IN718 alloy structure optimization method based on a three-dimensional wall-vibration controllable ultrasonic field device with patent number 202210440251.6 can be used. In the present invention, the material of the amplitude transformer can be selected as a Nb alloy rod with a diameter of 20 mm, which still has high strength at 1500°C.

[0059] In this embodiment, a cooling jacket is installed on the outer mold sleeve of the casting mold, and a cooling channel is provided between the cooling jacket and the casting mold. Cooling gas can be introduced into the cooling channel, and the cooling rate can be controlled by controlling the flow rate of the cooling gas. Nitrogen can be selected as the cooling gas.

[0060] In this embodiment, when step S3 is implemented, ultrasonic vibration acts on the whole solidification process including the primary γ phase, eutectic (γ+α) and γ′ precipitation phase, and the ultrasonic frequency is set to 20 kHz and the initial amplitude is 22 μm. Before the melt is poured into the mold, the device for implementing ultrasonic treatment is turned on, that is, the cylinder drive switch of the ultrasonic rod is turned on, the cylinder diameter is 40 mm, and the air pressures in the X, Y and Z directions are 1atm, 0.5atm and 1.5atm respectively, so that the end of the ultrasonic rod is against the outer wall of the mold, and the three-dimensional ultrasonic power supply is turned on synchronously to implement three-dimensional intermittent ultrasonic treatment in the X, Y and Z axes. When the temperature of the alloy melt drops to the alloy solidification temperature of 1315°C, the ultrasonic vibration is stopped, and then the alloy melt is controlled to cool to the γ′ phase precipitation start temperature of 1045°C at a cooling rate of 35°C / s, and then the ultrasound is turned on to apply three-dimensional intermittent ultrasound with an amplitude of 22μm. When the temperature of the alloy melt drops to the γ′ phase complete precipitation temperature of 865°C, the ultrasonic power supply is immediately turned off. At this time, nitrogen is injected into the cooling channel at a flow rate of 0.5L / min, and the alloy melt is controlled to cool to 600°C at a cooling rate of 20°C / s, so that the alloy is naturally cooled to room temperature in the air. The duration of a single ultrasonic treatment in intermittent ultrasound was 2 s, and the interval without ultrasonic vibration was 1 s.

[0061] In this embodiment, the heat treatment Ni in S4 50 Co 23 Cr 14 Al 13 In order to evenly distribute the eutectic (α+γ) structure, the alloy was placed in a tube furnace at room temperature and heated to 1100°C at a heating rate of 10°C / min. After keeping warm for 4 hours, the alloy was immediately taken out of the tube furnace and placed in quenching oil for oil quenching until the alloy cooled to room temperature.

[0062] In this embodiment, when the infrared thermometer of the crucible 2 detects that the melt temperature reaches 600° C., the high-frequency power supply of the high-frequency induction heating coil of the mold is turned on to preheat the mold. After the alloy melt in the crucible 2 is kept warm for 1 minute, the inner wall temperature of the mold is about 1000° C., the preheating power supply is turned off, and then the alloy melt is poured into the mold.

[0063] Comparative Example 1

[0064] This comparative example adopts the method in Example 1 to prepare Ni 50 Co 23 Cr 14 Al 13 alloy, the difference is that Ni50 Co 23 Cr 14 Al 13 When the alloy ingot is prepared, no ultrasonic treatment is applied and static solidification is used to prepare Ni 50 Co 23 Cr 14 Al 13 Alloy ingot.

[0065] Figure 1 The unheat-treated Ni prepared in Example 1 and Comparative Example 1 50 Co 23 Cr 14 Al 13 Alloy structure morphology pictures: (a) Comparative Example 1; (b) Example 1; (c) Ni prepared in Comparative Example 1 50 Co 23 Cr 14 Al 13 γ′ precipitation phase in the alloy; (d) Ni prepared in Example 1 50 Co 23 Cr 14 Al 13 A magnified image of the γ′ precipitation phase in the alloy. Figure 1 It can be seen that the alloy prepared in Comparative Example 1 is composed of γ dendrites, and the γ dendrites in the alloy prepared in Example 1 are significantly refined, and the size is 20% of that in Comparative Example 1. There is no (γ+α) eutectic in Comparative Example 1, while a (γ+α) eutectic structure with a volume fraction of 10% appears between the γ dendrites in the ultrasonically prepared alloy of Example 1. In Comparative Example 1, there is almost no γ′ phase inside the grains, but there is more γ′ at the grain boundaries. The comprehensive statistics show that the volume fraction and size of the γ′ phase are about 6% and 49nm, while the volume fraction of the γ′ phase in the ultrasonically prepared alloy of Example 1 is increased to 45%, and the size is about 61nm.

[0066] After testing, the unheat-treated Ni 50 Co 23 Cr 14 Al 13 The yield strength and tensile strength of the statically solidified alloy are 554 MPa and 720 MPa, respectively. 50 Co 23 Cr 14 Al 13 The yield and tensile strengths of the alloy are 780 MPa and 1080 MPa, respectively, which are 1.4 and 1.5 times that under static conditions.

[0067] Figure 2 The Ni prepared in Example 1 and Comparative Example 1 50 Co 23 Cr 14 Al13 DSC spectrum of the alloy. Figure 2 It can be seen that in comparative example 1, only γ phase is generated during the solidification stage, while in the embodiment, γ phase is generated first, and then eutectic reaction occurs to generate (γ+α) eutectic structure, indicating that ultrasound changes the phase transformation process of the alloy.

[0068] Figure 3 The Ni prepared in Example 1 and Comparative Example 1 50 Co 23 Cr 14 Al 13 Al element distribution of alloy: (a) Comparative Example 1; (b) Example 1. Figure 3 It is shown that the application of ultrasonic field in liquid alloy changes the segregation degree of Al in dendrites and between dendrites. Under static solidification, a large amount of Al element is segregated between dendrites of γ phase. After applying ultrasound, Al tends to be enriched in dendrites, strengthening the γ phase grain boundary.

[0069] Figure 4 The solidified and heat-treated Ni prepared in Example 1 50 Co 23 Cr 14 Al 13 Alloy structure morphology pictures: (a) solidified state; (b) heat treated state. Figure 4 It can be obtained that after keeping at 1100℃ for 4 hours, the (γ+α) eutectic at the γ phase grain boundary dissolved, and re-precipitated from the γ phase grains and was evenly distributed on the γ matrix, indicating that the heat treatment achieved the purpose of evenly distributing the (γ+α) eutectic structure.

[0070] Figure 5 The Ni prepared in Example 1 and Comparative Example 1 50 Co 23 Cr 14 Al 13 Tensile stress-strain curves of the alloy at room temperature (25°C) and high temperature (650°C): (a) Unheat-treated Ni prepared in Example 1 and Comparative Example 1 at room temperature 50 Co 23 Cr 14 Al 13 Tensile stress-strain curves of the alloy; (b) Unheat-treated Ni prepared in Comparative Example 1 and Example 1 at 650°C 50 Co 23 Cr 14 Al 13 Alloy, and the heat-treated Ni prepared in Example 1 50 Co 23 Cr 14 Al 13 Tensile stress-strain curves of the alloys; Figure 5The black line in (a) represents the unheat-treated Ni prepared in Comparative Example 1. 50 Co 23 Cr 14 Al 13 Tensile stress-strain curves of the alloy at room temperature; Figure 5 (a) The blue line in the figure represents the unheat-treated Ni prepared in Example 1. 50 Co 23 Cr 14 Al 13 Tensile stress-strain curves of the alloy at room temperature; Figure 5 The dark blue line in (b) represents the unheat-treated Ni prepared in Comparative Example 1. 50 Co 23 Cr 14 Al 13 Tensile stress-strain curve of the alloy at 650°C; Figure 5 The green line in (b) represents the unheat-treated Ni prepared in Example 1. 50 Co 23 Cr 14 Al 13 Tensile stress-strain curve of the alloy at 650°C; Figure 5 The red line in (b) indicates the Ni prepared in Example 1 after heat treatment. 50 Co 23 Cr 14 Al 13 Tensile stress-strain curve of the alloy at 650℃. Figure 5 It can be seen that the unheat-treated Ni prepared in Example 1 50 Co 23 Cr 14 Al 13 The tensile strength of the alloy reaches 1.08GPa, which is 1.5 times that of the static solidified alloy and significantly better than the commonly used cast nickel-based alloys such as IN718 and IN625. 50 Co 23 Cr 14 Al 13 The tensile strength of the alloy at a high temperature of 650°C is 672MPa, which is significantly higher than the high-temperature tensile strength of the cast IN718 alloy (550-580MPa); the tensile strength of the alloy after heat treatment at a high temperature of 650°C is 741MPa, which is better than the high-temperature tensile strength of the heat-treated IN718 alloy (~690MPa).

[0071] Example 2

[0072] This embodiment discloses an ultrasonic optimized Ni 50 Co 25 Cr 13Al 12 A method for determining the microstructure and properties of a high temperature alloy, the method comprising:

[0073] S1. Alloy smelting: Ni 50 Co 25 Cr 13 Al 12 The atomic ratio of the elements in the alloy is Co: 25%, Cr: 13%, Al: 12%, Ni: 50%, which are converted into the mass percentage of the elements. The surfaces of the raw material blocks are polished to be smooth, and the surface impurities are removed. Ni blocks, Co blocks, Cr blocks, and Al blocks with a purity of 99.99% are weighed respectively, and smelted and kept warm twice according to the mass percentage of each element.

[0074] The specific process of two smelting and heat preservation is as follows:

[0075] S101, first put Co block, Ni block and Cr block into crucible 1 in order, wherein the Cr block does not directly contact the inner wall of crucible 1, the material of crucible 1 is graphite, and crucible 1 needs to be sprayed with boron nitride coating before use, and put into vacuum high frequency furnace after loading, and embed two layers of graphite and mullite insulation sleeves outside crucible 1 respectively, and close the hatch after adjusting the position of infrared thermometer;

[0076] Then turn on the vacuum pump to evacuate to 10Pa, turn off the vacuum pump and fill the furnace with argon to 360Pa. After repeated vacuuming and filling 3 times, start the first smelting. The current of the high-frequency furnace is 18.4A. After heating for 8 minutes, the temperature reaches 1400℃. Thereafter, the temperature is observed every 0.5min. When the temperature reaches 1600℃, insulation is started. Heating is stopped after 3min. The alloy is cooled in the furnace for half an hour and then the raw materials are taken out to obtain Ni-Co-Cr intermediate alloy.

[0077] S102, first wrap the Ni-Co-Cr master alloy with aluminum foil, then put it into the crucible 2 sprayed with a high-temperature resistant coating, the material of the crucible 2 is graphite or corundum, and a layer of mullite insulation cover is nested outside the crucible 2, and the crucible 2 and the insulation cover are placed in a high-frequency coil and heated with a current of 35A; after the alloy is completely melted, use a long-handled spoon to add Al blocks to the melt and continue smelting. When the temperature of the melt in the crucible 2 reaches 1530°C, the high-frequency current is adjusted to 18A for insulation for 2 minutes to obtain an alloy melt, ready for pouring;

[0078] During smelting in S101 and S102, the temperature is detected by an infrared thermometer.

[0079] S2. Preheating the mold: first evenly apply boron nitride or zinc oxide mold release agent on the inner wall of the mold, heat it to 150°C with a hot air gun and dry it, then preheat the mold through the high-frequency induction heating coil with air atmosphere, and remove the high-frequency induction heating coil when the preheating temperature reaches 950°C;

[0080] The inner dimensions of the casting mold used are 20×20×50 mm, the wall thickness is 6 mm, and the material is TZM alloy.

[0081] During preheating, the high-frequency induction heating coil is placed horizontally at the center of the inner cavity of the mold. The outer diameter of the high-frequency induction heating coil is 15 mm, the height is 37.5 mm, the bottom of the coil is 5 mm away from the bottom of the mold, the high-frequency induction heating coil is coaxially arranged with the mold, and the infrared thermometer is aligned with the center of the mold.

[0082] S3. Preparation of Ni 50 Co 25 Cr 13 Al 12 Alloy ingot: Before pouring the melt, quickly remove the preheating high-frequency coil in the mold. Use crucible tongs to manually pour the alloy melt obtained from S1 from crucible 2 into the preheated mold, then perform ultrasonic vibration treatment with a frequency of 25kHz on the alloy melt in the mold, and control the cooling rate to finally obtain Ni 50 Co 25 Cr 13 Al 12 Alloy ingots;

[0083] When ultrasonic vibration acts only on the refinement of the primary γ phase, ultrasound is started before the alloy melt is poured into the casting mold, and one-dimensional ultrasound with an amplitude of less than 14 μm is applied. When the temperature of the alloy melt drops to the end temperature of the liquid-solid phase transition of 1377-1367°C, the ultrasonic vibration is stopped, and then the alloy melt is controlled to cool to 600°C at a cooling rate of not less than 30°C / s, and then naturally cooled to obtain Ni 50 Co 25 Cr 13 Al 12 Alloy alloy ingot;

[0084] In this embodiment, the liquid-solid phase transition end temperature is selected to be 1367° C., 1370° C. or 1377° C.; the cooling rate of the alloy melt can be 35° C. / s or 40° C. / s.

[0085] S4, the Ni obtained in S3 50 Co 25 Cr 13 Al 12 The alloy ingot is heat treated to further improve the Ni 50 Co 25 Cr 13 Al 12 The structure and properties of the alloy. The heat treatment is to uniformly distribute the eutectic (γ+α) structure of the alloy. The heat treatment temperature is 1150°C, the holding time is 4.5h, and the alloy is cooled in the furnace or naturally cooled in the air;

[0086] In this embodiment, step S2 performs temperature monitoring by an infrared thermometer, and step S3 uses a thermocouple to measure temperature.

[0087] In this embodiment, the preheated casting mold needs to be connected to a device that can implement ultrasonic vibration in three directions of X, Y, and Z axes. Specifically, the three-dimensional wall-vibration controllable ultrasonic field device disclosed in the IN718 alloy structure optimization method based on a three-dimensional wall-vibration controllable ultrasonic field device with patent number 202210440251.6 can be used. In the present invention, the material of the amplitude transformer can be selected as a Nb alloy rod with high strength at 1500°C and a diameter of 20 mm.

[0088] In this embodiment, a cooling jacket is installed on the outer mold sleeve of the casting mold, and a cooling channel is provided between the cooling jacket and the casting mold. Cooling gas can be introduced into the cooling channel, and the cooling rate can be controlled by controlling the flow rate of the cooling gas. Nitrogen can be selected as the cooling gas.

[0089] Example 3

[0090] This embodiment discloses an ultrasonic optimized Ni 54 Co 20 Cr 15 Al 11 A method for determining the microstructure and properties of a high temperature alloy, the method comprising:

[0091] S1. Alloy smelting: Ni 54 Co 20 Cr 15 Al 11 The atomic ratio of the elements in the alloy is Co: 20%, Cr: 15%, Al: 11%, Ni: 54%, converted into the mass percentage of the elements, each raw material block is polished and smoothed, and the surface impurities are removed. Ni blocks, Co blocks, Cr blocks, and Al blocks with a purity of 99.99% are weighed respectively, and smelted and kept warm twice according to the mass percentage of each element.

[0092] The specific process of two smelting and heat preservation is as follows:

[0093] S101, first put Co block, Ni block and Cr block into crucible 1 in order, wherein the Cr block does not directly contact the inner wall of crucible 1, the material of crucible 1 is graphite, and crucible 1 needs to be sprayed with boron nitride coating before use, and put into vacuum high frequency furnace after loading, and embed two layers of graphite and mullite insulation sleeves outside crucible 1 respectively, and close the hatch after adjusting the position of infrared thermometer;

[0094] Then turn on the vacuum pump to evacuate to 10Pa, turn off the vacuum pump and fill the furnace with argon to 360Pa. After repeated vacuuming and filling 3 times, start the first smelting. The current of the high-frequency furnace is 18.4A. After heating for 8 minutes, the temperature reaches 1400℃. Thereafter, the temperature is observed every 0.5min. When the temperature reaches 1550℃, insulation is started. Heating is stopped after 3min. The alloy is cooled in the furnace for half an hour and then the raw materials are taken out to obtain Ni-Co-Cr intermediate alloy.

[0095] S102, first wrap the Ni-Co-Cr master alloy with aluminum foil, then put it into the crucible 2 sprayed with a high-temperature resistant coating, the material of the crucible 2 is graphite or corundum, and a layer of mullite insulation cover is nested outside the crucible 2, and the crucible 2 and the insulation cover are placed in a high-frequency coil and heated with a current of 35A; after the alloy is completely melted, use a long-handled spoon to add Al blocks to the melt and continue smelting. When the temperature of the melt in the crucible 2 reaches 1570°C, the high-frequency current is adjusted to 18A for insulation for 1 minute to obtain an alloy melt, ready for pouring;

[0096] During smelting in S101 and S102, the temperature is detected by an infrared thermometer.

[0097] S2. Preheating the mold: first evenly apply boron nitride or zinc oxide mold release agent on the inner wall of the mold, heat it to 150°C with a hot air gun and dry it, then preheat the mold through the high-frequency induction heating coil with air atmosphere, and remove the high-frequency induction heating coil when the preheating temperature reaches 1150°C;

[0098] The inner dimensions of the casting mold used are 20×20×50 mm, the wall thickness is 6 mm, and the material is TZM alloy.

[0099] During preheating, the outer diameter of the high-frequency induction heating coil is 10 mm, the height is 30 mm, the bottom of the coil is 5 mm away from the bottom of the mold, the high-frequency induction heating coil is coaxially arranged with the mold, and the infrared thermometer is aligned with the center of the mold.

[0100] S3. Preparation of Ni 54 Co 20 Cr 15 Al 11 Alloy ingot: Before pouring the melt, quickly remove the preheating high-frequency coil in the mold. Use crucible tongs to manually pour the alloy melt obtained from S1 from crucible 2 into the preheated mold, then perform ultrasonic vibration treatment at a frequency of 17kHz on the alloy melt in the mold, and control the cooling rate to finally obtain Ni 54 Co 20 Cr 15 Al 11 Alloy ingots;

[0101] When the ultrasonic vibration in S3 acts only on the precipitation and growth of the γ′ phase, the alloy melt is poured into the mold, and when the temperature naturally drops to the precipitation temperature of the γ′ phase 1050-1035°C, the ultrasonic vibration is started, and ultrasound with an amplitude of 17μm is applied until the alloy melt temperature drops to the γ′ phase complete precipitation temperature 890-840°C, and the ultrasonic vibration is immediately turned off. At this time, the alloy melt is controlled to cool to 600°C at a cooling rate of 10-20°C / s, and then naturally cooled to obtain Ni 54 Co 20 Cr 15 Al 11 Alloy ingot; specifically, the γ′ phase precipitation start temperature can be selected to be 1035°C, 1045°C or 1050°C.

[0102] S4, the Ni obtained in S3 54 Co 20 Cr 15 Al 11 The alloy ingot is heat treated to further improve the Ni 54 Co 20 Cr 15 The structure and properties of Al1 alloy. If the heat treatment is to fully precipitate the nano-scale γ′ phase, the heat treatment temperature is 650°C and the holding time is 32 hours. After the holding is completed, the alloy is quickly taken out and placed in quenching oil to cool to room temperature.

[0103] In this embodiment, the heat treatment process may also be selected as follows: keeping the temperature at 800° C. for 16 hours.

[0104] In this embodiment, step S2 performs temperature monitoring by an infrared thermometer, and step S3 uses a thermocouple to measure temperature.

[0105] In this embodiment, the preheated mold needs to be connected to a device that can implement ultrasonic vibration in the three directions of X, Y, and Z axes. Specifically, a multi-directional coupled wall vibration three-dimensional ultrasonic metal solidification device with patent number 202110342358.2 can be used. The crucible 2 replaces its master alloy pool. The mold in the present invention is equivalent to its mold assembly. In the present invention, the material of its horn can be selected as a Nb alloy rod with high strength at 1500°C, with a diameter of 20mm. A pressing plate with an opening is used to fix the mold in the Z-axis direction. After the opening of the pressing plate is fully aligned with the mold opening, the screws of the pressing plate are tightened to form an antagonistic force with the Z-axis ultrasonic rod to prevent the mold assembly from moving.

[0106] In this embodiment, a cooling jacket is installed on the outer mold sleeve of the casting mold, and a cooling channel is provided between the cooling jacket and the casting mold. Cooling gas can be introduced into the cooling channel, and the cooling rate can be controlled by controlling the flow rate of the cooling gas. Nitrogen can be selected as the cooling gas.

[0107] Example 4

[0108] This embodiment is the same as the embodiment 3, except that: when the ultrasonic vibration acts on the primary γ phase refinement and the formation of the eutectic (γ+α) structure at the same time, the ultrasound is started before the alloy melt is poured into the casting mold, and the ultrasound with an amplitude of not less than 14 μm is applied. When the temperature of the alloy melt drops to the eutectic reaction L→γ+α end temperature of 1321-1311°C, the ultrasonic vibration is stopped, and then the alloy melt is controlled to cool to 600°C at a cooling rate of not less than 30°C / s, and then naturally cooled to obtain Ni 54 Co 20 Cr 15 Al 11 Alloy ingots;

[0109] The heat treatment in S4 is for uniformly distributing the eutectic (γ+α) structure, and the heat treatment temperature is 1050°C, the holding time is 4.5 hours, and the alloy is cooled in the furnace or naturally cooled in the air; or the heat treatment temperature is 1200°C, the holding time is 3.5 hours, and the alloy is cooled in the furnace or naturally cooled in the air.

[0110] In this embodiment, the alloy melt temperature drops to the end temperature of the eutectic reaction L→γ+α, which can be selected as 1311°C, 1321°C or 1315°C.

[0111] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for ultrasonically optimizing the structure and properties of Ni-Co based high temperature alloys, characterized in that: The Ni-Co based high temperature alloy is composed of the following components in atomic percentage: Co: 20-25%, Cr: 13-15%, Al: 11-13%, and the balance is Ni and unavoidable impurities; the method comprises: S1, Ni-Co based high temperature alloy smelting: Co block, Ni block and Cr block are taken in proportion and placed in crucible 1 for the first smelting and heat preservation, and a solidified Ni-Co-Cr master alloy is obtained after the first smelting and heat preservation, and then the Ni-Co-Cr master alloy and Al block are placed in crucible 2 for the second smelting and heat preservation to obtain an alloy melt; S2. Preheating the mold: first evenly apply boron nitride or zinc oxide release agent on the inner wall of the mold and dry it, then preheat the mold, the preheating temperature is higher than 900°C; S3. Ultrasonic optimization to prepare alloy ingots: The alloy melt obtained in S1 is poured from the crucible 2 into a preheated casting mold, and then the alloy melt in the casting mold is subjected to ultrasonic vibration treatment at a frequency of 17-25 kHz, and the cooling rate is controlled to finally obtain an alloy ingot.

2. The method for ultrasonically optimizing the structure and properties of a Ni-Co based high temperature alloy according to claim 1, characterized in that: The alloy ingot obtained in S3 is heat treated to further optimize the structure and properties of the Ni-Co based high temperature alloy.

3. The method for ultrasonically optimizing the structure and performance of a Ni-Co based high temperature alloy according to claim 1, characterized in that: The specific process of the first smelting and heat preservation is as follows: first, Co block, Ni block and Cr block are placed in order into the crucible 1, wherein the Cr block is not in direct contact with the inner wall of the crucible 1, the material of the crucible 1 is graphite or ceramic with a temperature resistance of more than 2000°C, the crucible 1 needs to be sprayed with a boron nitride coating before use, and the raw materials are melted under vacuum conditions, and the raw materials are completely melted and kept at 1550-1600°C for 3 minutes and then cooled with the furnace to obtain a Ni-Co-Cr master alloy; The specific process of the second smelting and heat preservation is: first wrap the Ni-Co-Cr master alloy with aluminum foil, then put it into the crucible 2 sprayed with a high-temperature resistant coating, the material of the crucible 2 is graphite or corundum, and smelt it in the air. After the master alloy is completely melted, put the Al block into the melt, and keep it at 1530-1570°C for 1-2 minutes to obtain an alloy melt.

4. The method for ultrasonically optimizing the structure and properties of a Ni-Co based high temperature alloy according to claim 1, characterized in that: In S3, according to the requirements of the metallographic structure of the alloy, there are four ways to treat the alloy melt by ultrasonic vibration, and different cooling control methods are combined, specifically: First, when ultrasonic vibration acts only on the refinement of the primary γ phase, ultrasonic vibration is started before the alloy melt is poured into the casting mold, and one-dimensional ultrasound with an amplitude of less than 14 μm is applied. When the temperature of the alloy melt drops to the end temperature of the L→γ liquid-solid phase transition of 1377-1367°C, the ultrasonic vibration is stopped, and then the alloy melt is controlled to cool to 600°C at a cooling rate of not less than 30°C / s, and then naturally cooled to obtain an alloy ingot; Second, when ultrasonic vibration acts on the refinement of the primary γ phase and the formation of the eutectic (γ+α) structure at the same time, the ultrasonic vibration is started before the alloy melt is poured into the casting mold, and ultrasound with an amplitude of not less than 14 μm is applied. When the temperature of the alloy melt drops to the eutectic reaction L→γ+α end temperature of 1321-1311°C, the ultrasonic vibration is stopped, and then the alloy melt is controlled to cool to 600°C at a cooling rate of not less than 30°C / s, and then naturally cooled to obtain an alloy ingot; Third, when ultrasonic vibration only acts on the precipitation and growth of γ′ phase, after pouring the alloy melt into the casting mold, when the temperature naturally drops to the precipitation temperature of γ′ phase 1050-1035°C, ultrasonic vibration is started, and ultrasound with an amplitude of not less than 14μm is applied until the alloy melt temperature drops to the complete precipitation temperature of γ′ phase 890-840°C, and ultrasonic vibration is immediately turned off. At this time, the alloy melt is controlled to cool down to 600°C at a cooling rate of 10-20°C / s, and then naturally cooled to obtain an alloy ingot; Fourthly, when ultrasonic vibration acts on the whole process of primary γ phase, eutectic (γ+α) solidification and precipitation and growth of γ′ phase, ultrasonic vibration is turned on before the alloy melt is poured into the casting mold, and intermittent ultrasound with an amplitude of not less than 14 μm is applied. When the temperature of the alloy melt drops to the alloy solidification temperature of 1321-1311°C, the ultrasonic vibration is stopped, and then the alloy melt is controlled to be cooled to the γ′ phase precipitation start temperature of 1050-1035°C at a cooling rate of not less than 30°C / s, and then ultrasonic vibration is turned on again, and intermittent ultrasound with an amplitude of not less than 14 μm is applied. When the temperature of the alloy melt drops to the γ′ phase complete precipitation temperature of 890-840°C, the ultrasonic vibration is immediately turned off, and finally the alloy melt is controlled to be cooled to 600°C at a cooling rate of 10-20°C / s, and then naturally cooled to obtain an alloy ingot.

5. The method for ultrasonically optimizing the structure and properties of a Ni-Co based high temperature alloy according to claim 4, characterized in that: The intermittent ultrasound is a process in which an interval without applying ultrasonic vibration is set between multiple ultrasonic treatments, a single ultrasonic treatment lasts for 1-5 seconds, and the interval without applying ultrasonic vibration does not exceed 1 / 2 of the single ultrasonic treatment time.

6. The method for ultrasonically optimizing the structure and properties of a Ni-Co based high temperature alloy according to claim 2, characterized in that: If the heat treatment is to uniformly distribute the eutectic (γ+α) structure, the heat treatment temperature is 1050-1200°C, the holding time is 3.5-4.5h, and the alloy is cooled in the furnace or naturally cooled; If the heat treatment is to promote the precipitation and growth of nano-scale γ′ phase, the heat treatment temperature is 650-800° C., the insulation time is 16-32 hours, and after the insulation is completed, the alloy is quickly taken out and placed in quenching oil to cool to room temperature.

7. The method for ultrasonically optimizing the structure and properties of a Ni-Co based high temperature alloy according to claim 1, characterized in that: The outer mold sleeve of the casting mold is provided with a cooling sleeve through which cooling gas passes.

8. The method for ultrasonically optimizing the structure and properties of a Ni-Co based high temperature alloy according to claim 1, characterized in that: The casting mold described in S2 is preheated by a high-frequency induction heating coil, the maximum diameter of the high-frequency induction heating coil is 5-10mm smaller than the side length of the inner cavity of the casting mold, and the height of the high-frequency induction heating coil is 60-75% of the inner height of the casting mold; during preheating, the high-frequency induction heating coil is placed in the center of the inner cavity of the casting mold in the horizontal direction and 3-5mm away from the bottom of the casting mold in the vertical direction.

9. A method for ultrasonically optimizing the structure and properties of a Ni-Co based high temperature alloy according to claim 1 or 2, characterized in that: S1 and S2 use infrared thermometers, and S3 uses thermocouples to monitor temperature changes.

Citation Information

Patent Citations

  • Multidirectionally-coupled wall-surface-vibration three-dimensional ultrasonic metal solidification device and method

    CN113102733A

  • IN718 alloy structure optimization method based on three-dimensional wall vibration type controllable ultrasonic field device

    CN114774820A

Cited By

  • Method for improving as-cast solidification quality of Inconel718 high-temperature alloy and alloy cast ingot thereof

    CN121272239A